a) 65-a=(4x6+36:9):7+2x:8
65-a=(24+4):7+2
65-a=28:7+2
65-a=4+2
65-a=6
65-6=a
59=a
c) 36 : 6 x c = 9 x 4 - 4 x 5 + 2
6c= 36-20+2
6c=16+2
6c=18
c=[tex] \frac{18}{6} [/tex]=3
d) d : 3 = 53 - 36 : 4 x 5
d:3=53-45
d:3=8
d=8x3
d=24
e) 32 : e =( 36 : 6 + 42 : 7) - 4 x 2
32:e=(6+6)-8
32:e=12-8
32:e=4
e=[tex] \frac{32}{4} [/tex]=8
f) f -( 56 + 4 x 2 - 14 : 2 )= 24 : 8 +32 :8 + 36
f-(56+8-7)=3+4+36
f-54= 43
f= 43+57
f=100
g) 33 - 40 : 2 + 4 x 8 + 7 x 7 - 74 + g = 4 x 6
33-20+32+49-74+g=32
20+g=32
g=32-20
g=12